Research into composition and properties of the Ni–Fe electrolytic alloy - Sknar, Yuri; Sknar, Irina; Cheremysinova, Anna; Yermolenko, Iryna; Karakurkchi, Ann; Mizin, Vitaly; Proskurina, Valeriya; Sachanova, Yuliya (Eastern-European Journal of Enterprise Technologies, 2017)
Promising yet insufficiently studied is the new electrolyte based on methanesulfonate salts of the alloy-forming metals. Examining the laws that govern the electrodeposition of the Ni–Fe alloy with assigned physical-chemiсal properties from the methanesulfonate electrolyte is a relevant task. In the present work we established influence of the concentration of iron(ІІ) ions in the electrolyte and of current density on the composition of alloy. The content of iron in the Ni–Fe alloy grows with an increase in the concentration of iron(ІІ) ions in the methanesulfonate electrolyte. Dependence of the content of iron in the alloy on current density is of extreme character. The maximum corresponds to the current density of 1 A/dm2. It is shown that the organic additive applied in the present work, sodium saccharinate, does not exert any substantial influence on the composition of alloy at current density exceeding 2 A/dm2. Sodium saccharinate increases microhardness of the coating with the Ni–Fe alloy whose values reach 500 kg/cm2. When introducing into the methanesulfonate deposition electrolyte of the Ni–Fe alloy of 6 mmol/l of sodium saccharinate, practically unstressed precipitations precipitate. A reduction in the internal stresses leads to a decrease in the values of coercive force of the alloy. It is demonstrated that the investigated properties of the Ni–Fe precipitations are determined by the structure of coatings. Sodium saccharinate, being a surface-active compound under the conditions of electrolysis, changes the structure of the cathodic Ni–Fe alloy and improves functional characteristics of coatings. The established dependences represent a rather valuable basis for designing new technologies of the electrodeposition of polyfunctional coatings with the Ni–Fe alloy with enhanced mechanical and magnetic characteristics